Assessment of basic physical parameters of current Canadian-American National Hockey League (NHL) ice hockey players - Martin Sigmund; Steven Kohn; Dagmar Sigmundová (Acta Gymnica, 2016)
Background: Physical parameters represent an important part of the structure of sports performance and significantly contribute to the overall performance of an ice hockey player. Basic physical parameters are also an essential part of a comprehensive player assessment both during the initial NHL draft and further stages of a professional career. For an objective assessment it is desirable to know the current condition of development of monitored somatic parameters with regard to the sports discipline, performance level and gaming position. Objective: The aim of this study was to analyze and present the level of development of basic physical characteristics [Body Height (BH) and Body Weight (BW)] in current ice hockey players in the Canadian-American NHL, also with respect to various gaming positions. Another aim is to compare the results with relevant data of elite ice hockey players around the world. Methods: The data of 751 ice hockey players (age range: 18-43 years; 100% male) from NHL (2014/2015 season) are analyzed (goalkeepers, n = 67; defenders, n = 237; forwards, n = 447). Statistical data processing was performed using a single factor ANOVA and Fisher's (LSD) post hoc test. The level of statistical significance was tested at a level of p ≤ .05; p ≤ .01. Effect size was expressed according to Cohen's d. Results: Current levels of monitored parameters of NHL players represent the values: BH = 186.0 ± 5.3 cm, BW = 91.7 ± 6.9 kg. Significant differences among positions were found for the BH (goalkeepers > defenders > forwards) and BW (defenders > goalkeepers > forwards). Differences among forwards positions were also found for the BH (left wings > right wings > centers) and BW (left wings > right wings > centers). Conclusion: The observed values represent the current level of basic physical parameters in professional ice hockey players in the NHL and can be considered reference values in this specific population group.